Through the looking-glass: microscopy techniques for studying mitochondria - Rivas Carrillo, Salvador (My University, 2022)
Mitochondria are essential organelles of eukaryotic animal cells, representing the powerhouses fueling all cellular processes. Despite their fundamental importance for eukaryotic life, some aspects of their physiology remain obscure or poorly studied, partially due to technological limitations. For example: 1) transcellular degradation of mitochondria from one cell by another cell, transmitophagy, which has been observed in neurons and that is hypothesized to add to the known mechanisms of mitochondrial degradation, apoptosis and intracellular mitophagy; 2) the spatial association between Twinkle helicase, a protein indispensable for mitochondrial DNA replication, and mitochondrial-associated membrane structures, fatty-rich dynamic structures implicated in contact points with endoplasmic reticulum. In this thesis, I collected more than 150 transmission electron microscopy images and established experimental parameters for fluorescence microscopy section of correlative light electron microscopy to study transmitophagy. Moreover, I established experimental parameters on sample preparation and staining when using fluorescence microscopy and immuno transmission electron microscopy with silver - nano gold coating to study mitochondrial DNA replication. Thus, this work aided in establishing experimental setups for available imaging techniques, which have added to the existing repertoire of tools to study mitochondria.
Keywords: Electron microscopy, mitochondria